The preservation of provincial identity in baroque influenced artistic architectural structure at Kampung Cina, Terengganu - Nurkhazilah Idris,; Tengku Intan Suzila T.S.,; Liza Marziana Mohammad, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The states in the east of peninsular Malaysia are rich with unique cultural heritage. Congruently, Terengganu has a hidden treasure that has qualified it to be gazetted as one of the Malaysian heritage sites. The western Baroque artistic architectural is proposed as an analytical discussion in this article pertaining to the classical appreciation that are impressively portrayed on buildings at Kampung Cina, Kuala Terengganu. This study pursues to unfold the spectrum of the classical artistic western Baroque architectural elements’ influences, unfolding how stylization approach is incorporated, and to describe how provincial identity is preserved on buildings on the selected commercial buildings in Kampung Cina. The present study adopted qualitative approach with convenience sampling of the Kampung Cina, Terengganu buildings. Through visual evidence method, findings are revealed based on the simplistic visual impressionistic content comparison analysis. The findings suggest some strong evidence of geographical impact in relation to European Baroque inspirations that exist on these buildings. Yet, the complexity of the relationship with the local characteristics have commemorated this European flare. The intricacy of the relationship between provincial identity and colonialization is moderated by environmental characteristics which serve as an integral component in guiding the relationship between provincial identity to the state of great sophistication with the element of colonialization. Thus, the present study serves as a knowledge gateway to how colonial idealistic manifestation has impacted the local scene and how it has been mellowed by harmonization of strength and perseverance of provincial identity.